THE NEED FOR ANTHROPOCENTRIC APPROACH TO TEACHING THE UZBEK LANGUAGE (World Bulletin of Social Sciences, 2025)
Teaching language in a multilingual and multicultural environment requires a deep understanding of the psycholinguistic and pragmatic features that affect the learning process. This article discusses the psycholinguistic and pragmatic aspects of teaching language in a multilingual and multicultural environment. The article examines how the main concepts and phenomena theoretically studied in psycholinguistics and pragmatics manifest themselves in the process of teaching the Uzbek language, in particular in teaching the language in a multilingual and multicultural environment. Conclusions and proposals for effective teaching and learning of the Uzbek language in a multilingual and multicultural environment are given